New fossil leaves and fruits of Lauraceae from the Middle Miocene of Fujian, southeastern China differentiated using a cluster analysis. (28th May 2019) - Wang, Zixi; Sun, Fankai; Wang, Jidong; Yan, Defei; Dong, Junling; Sun, Mingxuan; Sun, Bainian
Abstract: The fossil record of Lauraceae can be traced back to the Early Cretaceous of eastern Asia based on fossil flowers. Here, we refer a number of new occurrences of leaf and fruit fossils of Lauraceae from the Middle Miocene of Zhangpu, Fujian, China, to seven species. These data provide evidence supporting the fact that a diverse subtropical, or tropical, Lauraceae-dominated evergreen forest surrounded this region 15 million years ago (Mya). The Lauraceae fossils presented in this paper provide evidence for the evolution of this group as well as new materials that enable the study of the Fujian Province Neogene flora. The fossils described in this paper fill in the gaps in studies about Lauraceae pollen in the Middle Miocene from Fotan, Fujian, China. In addition, these fossils also enrich the Middle Miocene fossil records of Lauraceae in eastern Asia, especially improving the study of the macrostructures and reproductive organs of fossil Lauraceae from southern China. The similarity between fossil and modern fruits shows that during the Middle Miocene the fruit morphological of Lauraceae have changed very little. We also identify families where the fossils we report belong to their closest relatives and can be used to reconstruct the paleoenvironment of Fujian in the Middle Miocene.